Migranten zonder verblijfsvergunning Rechten en sociaaleconomische positie in Nederland - Berntsen, Lisa (Amsterdam University Press, 2022)
Despite attempts by the Dutch government to combat and discourage unlawful residence, there are people who live in the Netherlands without a residence permit. However, little is known about the way they live (or survive) and work in the Netherlands. Although their residence is not legal, this does not mean that migrants without residence permits have no rights. On the contrary, this book connects the legal legislation and regulations on the national and international level with the socio-economic reality of this vulnerable group of migrants. Based on unique empirical material, this study shows the discrepancy between the rights that also apply to migrants without residence permits, for example as workers, as patients or as residents, and shows the absence of protection in everyday practice. The book concludes with an exploration of possibilities for improving the vulnerable position of migrants without residence permits in the Netherlands.